Occupational Stress Among Nurses: An ENSS-Based Analysis at X Hospital, Boyolali in 2024 - Zakki Saefurrohim, Muhamad; Mukti Wibawani, Eprami (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
According to a survey by the Indonesian National Nurses Association (PPNI) in 2018, around 50.9% of nurses in Indonesia experience work stress. This study aims to identify factors that cause work stress in nurses based on the Expanded Nursing Stress Scale (ENSS), which consists of nine subscales: Death and Dying, Conflict with Doctors, Insufficient Preparation, Problems with Coworkers, Problems with Supervisors, Uncertainty of Treatment, Problems with Patients, Workload, and Discrimination. This study used a cross-sectional study design with a total sample of 76 nurses, Data analysis used PLS-SEM and bootstrapping methods. The results showed that the three main constructs contributing to the highest job stress were Problems with Supervisors (β = 0.224; p = 0.000), Workload (β = 0.211; p = 0.000), and Treatment Uncertainty (β = 0.201; p = 0.000), while Discrimination showed no significant effect (p = 0.232). Problems with Supervisors, Workload, and Treatment Uncertainty are the causes of job stress in nurses at X Hospital, Boyolali in 2024